2017
DOI: 10.2399/ana.16.047
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric assessment of sella turcica using CT scan

Abstract: Sella turcica is a saddle-shaped depression located in the middle cranial fossa on the upper surface of the sphenoid bone. It is enclosed by the pituitary fossa in which the pituitary gland is lodged, tuberculum sellae on the front and dorsum sellae in the rear. [1][2][3][4] Two anterior and two posterior clinoid processes form a protrusion on the pituitary fossa, and these are the structures that protect the pituitary gland in the sella turcica. The extensions of the sphenoid bone's ala minor to the anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…The typical size of ST differs according to the individual's ethnicity, geography, and race [13,14]. Many studies have shown that the altered morphology of ST is usually associated with some severe pathological conditions, including pituitary tumours, hypoactive pituitary, Down syndrome, and Williams syndrome [15][16][17]. Srinivas et al [19] also agreed on the correlation between the altered morphology of ST and the presence of related pathological conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The typical size of ST differs according to the individual's ethnicity, geography, and race [13,14]. Many studies have shown that the altered morphology of ST is usually associated with some severe pathological conditions, including pituitary tumours, hypoactive pituitary, Down syndrome, and Williams syndrome [15][16][17]. Srinivas et al [19] also agreed on the correlation between the altered morphology of ST and the presence of related pathological conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly; metric measures of Sella Turcica show a wide range of variability among different populations in relation to sex. For example, Turamanlar et al (2017) in Turkish population; Chou et al (2021Chou et al ( , 2022 in Taiwanese population and El-Sehly et al (2018) in Egyptian population; revealed evident difference in Sella measurements between both sexes. On the other hand; Islam et al (2017) in Bangladeshi population and Hasan et al (2016b) in Iraqi population; reported non-significant difference between males and females as regard Sella measures.…”
Section: Introduction mentioning
confidence: 95%
“…Images were randomly selected from images stored on picture archiving and communication system (PACS) system scans of Mansoura University Hospitals during the period between September 2021 and March 2022 after applying the exclusion criteria. Age of the enrolled subjects ranged between 18 and 70 years (Turamanlar et al, 2017;Silveira et al, 2020). All participants had skull CT for different diagnostic medical or surgical reasons and no unnecessary exposure to radiation was done for the research purpose.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
See 2 more Smart Citations